From portable dialysis to a bioengineered kidney. (4th May 2018) - van Gelder, Maaike K.; Mihaila, Silvia M.; Jansen, Jitske; Wester, Maarten; Verhaar, Marianne C.; Joles, Jaap A.; Stamatialis, Dimitrios; Masereeuw, Roos; Gerritsen, Karin G. F.
ABSTRACT: Introduction : Since the advent of peritoneal dialysis (PD) in the 1970s, the principles of dialysis have changed little. In the coming decades, several major breakthroughs are expected. Areas covered : Novel wearable and portable dialysis devices for both hemodialysis (HD) and PD are expected first. The HD devices could facilitate more frequent and longer dialysis outside of the hospital, while improving patient's mobility and autonomy. The PD devices could enhance blood purification and increase technique survival of PD. Further away from clinical application is the bioartificial kidney, containing renal cells. Initially, the bioartificial kidney could be applied for extracorporeal treatment, to partly replace renal tubular endocrine, metabolic, immunoregulatory and secretory functions. Subsequently, intracorporeal treatment may become possible. Expert commentary : Key factors for successful implementation of miniature dialysis devices are patient attitudes and cost-effectiveness. A well-functioning and safe extracorporeal blood circuit is required for HD. For PD, a double lumen PD catheter would optimize performance. Future research should focus on further miniaturization of the urea removal strategy. For the bio-artificial kidney (BAK), cost effectiveness should be determined and a general set of functional requirements should be defined for future studies. For intracorporeal application, water reabsorption will become a major challenge.